Pushing the photodelivery of nitric oxide to the visible: are {FeNO}7 complexes good candidates?. Issue 46 (9th November 2017) - Levin, Natalia; Perdoménico, Julián; Bill, Eckhard; Weyhermüller, Thomas; Slep, Leonardo D.
Abstract : The photoactivity displayed by the newly prepared [Fe((CH2 Py2 )2 Me[9]aneN3 )(NO)](BF4 )2 suggests that FeNO 7 octahedral coordination compounds may be employed for controlled NO-photorelease. Abstract : Photodelivery of NO requires stable compounds which can be made reactive by irradiation with (visible) light. Traditional MNO 6 complexes require a substantial ligand design to shift their absorption spectra to the appropriate region of the electromagnetic spectrum. [Fe((CH2 Py2 )2 Me[9]aneN3 )(NO)](BF4 )2 is a new FeNO 7 octahedral coordination compound, which is thermally and air-stable in solution. Illumination with a 450 nm light source induces significant photodetachment of the coordinated NO ( ϕ NO = 0.52 mol einstein −1 ), suggesting that FeNO 7 compounds can be in fact suitable compounds for therapeutic NO-photorelease.